DE PROFESSORA À PESQUISADORA: A FORMAÇÃO DA IDENTIDADE DOCENTE NO ENSINO SUPERIOR - Soares, Marisa (2010)
This search refers to the formation of teacher identity in higher education that is characterized by the inseparabilty between teaching, research and extension. The methodology used is the Oral History, through oral histories of life of four teachers who teach in graduate school at a private university. The main theoretical foundations are: António Nóvoa, (1988, 2009), Luis Antonio Cunha (1980, 1997), Dermeval Saviani, (2001), Antonio Joaquim Severino, (2001), Carlos Benedito Martins, (1981, 2002), Gaston Pineau, (2006), and Maria Isaura de Pereira Queiroz, (1988, 1999, 2010). The notion of professional identity comes from the positions and views attributed to different discourses and social agents to teachers in performing their various teaching activities in different contexts, therefore, in different educational institutions. The practice of teaching in higher education is analyzed and the knowledge of this profession, which both allow the formation of future teachers with a view of the importance of scientific methodology, and provides a leap in quality and continuous updating in keeping with the requirements of higher education, attached to the importance of social responsibility.